Effects of Platelet Rich Plasma and Hydroxyapatite Implants Derived from Cuttlefish Bone (Sepia Sp) on Bone Generation and Osteogenic Activity - Sofia, Sofia; Firdaus, Azhar; Erwin, Erwin; Hayati, Zinatul (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Bone defects require biocompatible biomaterials that support osteoconduction and tissue regeneration. Hydroxyapatite (HA) derived from cuttlebone (Sepia sp.) offers high calcium content and a porous structure with potential as a bone implant, while Platelet Rich Plasma (PRP) contains growth factors that enhance regeneration. This study aimed to evaluate the effects of PRP and cuttlebone HA on bone defect healing in rats using histopathological features. Nine male Wistar rats were divided into three groups: K1 (negative control), K2 (HA + PRP), and K3 (HA). Alveolar bone defects (5 mm in diameter) were surgically created, and treatments were applied accordingly. Samples were evaluated on day 30 using hematoxylin eosin staining and histomorphometric analysis. Parameters assessed included osteoblast, osteocyte, and osteoclast counts and neovascularization in the implant bone. One-way ANOVA revealed significant differences in osteoblast (p-value =0.000), osteoclast (p-value =0.033), and osteocyte (p-value =0.001) counts across groups. Kruskal-Wallis test showed significant difference in neovascularization (p-value =0.047). Histopathological examination demonstrated no necrosis and increased bone marrow proliferation in the K2 group. This study indicates that cuttlebone-derived hydroxyapatite holds potential as a regenerative implant, particularly when combined with PRP